2015
DOI: 10.1155/2015/464376
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Infectious Bursal Disease Virus Using Indigenous Chicken Embryos in Kenya

Abstract: Infectious bursal disease virus (IBDV) isolates were recovered from outbreaks to initiate activities towards developing a local vaccine strain. Use of indigenous chicken embryos was exploited to determine their potential, promote utilization of local resources for research, and enhance household economic activities. Bursa of Fabricius (BFs) samples from outbreaks shown to be IBDV positive was homogenized and inoculated in 4-week-old specific pathogen-free (SPF) IBDV seronegative white leghorn chicks. The harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Oedematous CAMs were observed with or without congestion or haemorrhages. Similar pathological lesions Mutinda et al (2015), with numerical differences only. The higher sensitivity of RT-PCR than that of egg embryo inoculation was ability of RT-PCR to amplify viral nucleic acid from both complete and disintegrated viruses.…”
Section: Resultsmentioning
confidence: 83%
“…Oedematous CAMs were observed with or without congestion or haemorrhages. Similar pathological lesions Mutinda et al (2015), with numerical differences only. The higher sensitivity of RT-PCR than that of egg embryo inoculation was ability of RT-PCR to amplify viral nucleic acid from both complete and disintegrated viruses.…”
Section: Resultsmentioning
confidence: 83%
“…Similarly, Daodu et al (2018) reported 100% IBDV antibody in Egypt's unvaccinated birds/morbid birds. Mutinda et al (2015) reported that IBD mortality rates from 1.3-100% in flocks of Kenya indigenous chickens with an average mortality of 39.2%, high (31.1%) in layers, and 13.4% in broilers. From India (Singh and Dhawedkar 1994), Taiwan (Tsai and Lu 1993), and Ethiopia (Wakgari 2022), seroprevalence of IBDV has been reported to be 46.2, 45 and 43.13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Bursa of Fabricius samples were prepared according to Mutinda et al . [ 43 ] and stored in 2 mL Eppendorf tubes at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty samples (bursa of Fabricius) were collected from chickens suspected of having Gumboro disease (IBD) in various areas of Iraq's Baghdad government. Bursa of Fabricius samples were prepared according to Mutinda et al [43] and stored in 2 mL Eppendorf tubes at −20°C until use.…”
Section: Sample Collectionmentioning
confidence: 99%